Effects of a Clinic-Based Exercise Program on Sleep Disturbance Among Cancer Survivors. (November 2020) - Hidde, Mary C.; Leach, Heather J.; Marker, Ryan J.; Peters, John C.; Purcell, W. Thomas
Introduction: Sleep disturbance is the second leading negative side effect reported by cancer survivors, and evidence exists to suggest that exercise may improve sleep for cancer survivors. This study examined changes in sleep following a 3-month, clinic-based exercise program among a diverse group of cancer survivors. Methods: Single group, pre-post study design. Participants were enrolled in a supervised exercise program which consisted of moderate intensity aerobic and resistance training, twice per week for 3-months. To be eligible, individuals had to be diagnosed with cancer, and undergoing, or within 6-months of completing chemo and/or radiation therapy. Sleep was assessed at pre-and post-program using 3 self-report questions as part of a standard wellness assessment conducted at the program's facility. Changes in categorical outcomes were evaluated using McNemar and Wilcoxon Signed-Rank Tests. Results: Participants ( N = 94) were mostly female (68.1%, N = 64), mean age = 54.26 ± 14.26 (20-78), and diagnosed with more than 8 different cancer types. Half ( N = 48, 51.1%) of participants improved on 1 or more of the questions assessing sleep. At post-program, 39% of participants reported that they did not awaken feeling rested versus 48% at pre-program ( P = .08). At post-program, 47% reported awakening ≥1 time per night versus 46% at pre-program ( P = .97), and 17% reported poor or very poor sleep quality at post-program versus 24% at pre-program ( P = .16). There were no differences in demographic, cancer-related, psychosocial, and physical fitness variables between participants who improved on any of the questions assessing sleep versus those who did not. Conclusions: A clinically implemented exercise program may help some cancer survivors improve sleep, however more studies utilizing validated, objective measures of sleep are needed to confirm effectiveness.